History and development of national burden of disease assessment in Australia - Lynelle Moon; Michelle Gourley; John Goss; Miriam Lum On; Paula Laws; Anna Reynolds; Richard Juckes (BMC, 2020)
Abstract Australia's 1996 national burden of disease (BoD) study was one of the first in the world and updates have continued over the following two decades with the fifth study now underway. The studies adapt the global framework most recently implemented by the Global Burden of Disease Study and the World Health Organization to suit Australia's specific needs, producing estimates of fatal and non-fatal burden via the Disability Adjusted Life Year (DALY) metric, as well as attribution of the burden to many risk factors. Detailed Australian data are used with minimal reliance on modelling to fill data gaps. Comprehensive estimates are produced, including for the Indigenous population, for each of the eight states and territories, the five remoteness areas and five socioeconomic quintiles. A number of method developments have been made as part of these studies, including redistribution of deaths data and a detailed quality framework for describing the robustness of the underlying data and methods. Data and methods continue to be refined as part of the studies, and developments in global studies and other national studies are incorporated where appropriate.